A ANALYSIS OF PREPARATIONS FOR THE IMPLEMENTATION OF ELECTRONIC MEDICAL RECORDS AT RSJ PROF HB SAANIN PADANG USING THE DOQ-IT METHOD - Nurul Fitri Khumaira; Annisa Wahyuni; Yuli Mardi (AKADEMI PEREKAM DAN INFORMASI KESEHATAN (APIKES) IRIS PADANG, 2023)
According to PMK No. 24 of 2022, a medical record is a document containing data on patient identity, examination, treatment, actions, and other services that have been provided to the patient. Through this policy, health service facilities are required to run an electronic patient medical history recording system. The transition process is carried out until no later than 31 December 2023. This type of research uses quantitative methods. Quantitative research methods are used to determine the picture of hospital readiness. The method used to analyze hospital readiness is DOQ-IT with indicators of organizational culture readiness, governance and leadership readiness, human resource readiness, and infrastructure readiness. Based on the results of the research that has been carried out, information can be obtained that in the aspects of human resources, organizational work culture, leadership governance, and infrastructure as a whole can be seen from the answers of 18 ready respondents (46.06%) and very ready as many as 20 people (49.87%) then with the respondent's answer not ready as many as 1 person (2.22%) the answer is very unprepared as many as 1 person (0.35%) and for the answer hesitant as many as 1 person (1.44%), it is confirmed from the informant that the preparation for the implementation of electronic medical records is ready to be implemented.